(untitled) (Fiep Bulletin - online, 2013)
AIDS epidemic presents today, in Brazil, among its prominent features, the feminization, which concerns the increasing participation of women in the total of registered cases in the country. The heterosexual relation is the main transmission that has contributed to the epidemic feminization. Therefore, the objective of this study was to trace the epidemiological profile of women living with HIV / AIDS attended in a reference service for the AIDS treatment. It is an epidemiological study, descriptive and quantitative analytical in nature, developed at the clinic of Giselda Trigueiro Hospital (HGT), a reference to treat AIDS, located in Natal - RN / Brazil. The sample comprised 33 women with HIV, registered and treated in this reference center. As main results, it was observed that women with HIV were in the range between 20 and 36 years, with an average age of 28 years. They came from Natal, 18 (54.55%). About the family income, 17 (51.5%) had a minimum wage, 11 (33.33%) two salaries and 5 (15.15%) had no income. The group had as prevalent form of contamination, the route of heterosexual transmission 25 (75.8%), from stable partner. Regarding education, we observed that the majority had the elementary school (18), representing 54.5% of the interviewees. It can be concluded that this survey, which interviewed women were mostly young, low income, with little schooling, and contaminated by unprotected heterosexual relationship, following the trend of the epidemic in Brazil and abroad.